2013
DOI: 10.1016/j.contraception.2013.05.127
|View full text |Cite
|
Sign up to set email alerts
|

Provider self-disclosure during contraceptive counseling

Abstract: Objective(s)-Provider self-disclosure (PSD) -defined as providers making statements regarding personal information to patients -has not been well-characterized in the context of contraceptive counseling. In this study we describe the incidence, content and context of contraceptive PSD.Study Design-This mixed methods analysis used data from the Provider-Patient Contraceptive Counseling study, for which 349 family planning patients were recruited from 2009 to 2012 from six clinics in the San Francisco Bay Area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This type of self-disclosure is a controversial topic in the health communication literature in general, as it can be seen, on one side, as enhancing the therapeutic relationship, or, alternatively, as a transgression of professional boundaries and an inappropriate distraction from the needs and experiences of the patient. Evidence from one study in family planning suggests that this type of disclosure is generally perceived to be appropriate by patients and contributes positively to the counseling dynamic, 42 which is consistent with patients’ desire for a closer personal connection with their provider in this context. The power of self-disclosure during contraceptive counseling is highlighted by a study that found that self-disclosure of IUD use increases uptake of this method.…”
Section: What Are Best Practices For Contraceptive Counseling?mentioning
confidence: 75%
“…This type of self-disclosure is a controversial topic in the health communication literature in general, as it can be seen, on one side, as enhancing the therapeutic relationship, or, alternatively, as a transgression of professional boundaries and an inappropriate distraction from the needs and experiences of the patient. Evidence from one study in family planning suggests that this type of disclosure is generally perceived to be appropriate by patients and contributes positively to the counseling dynamic, 42 which is consistent with patients’ desire for a closer personal connection with their provider in this context. The power of self-disclosure during contraceptive counseling is highlighted by a study that found that self-disclosure of IUD use increases uptake of this method.…”
Section: What Are Best Practices For Contraceptive Counseling?mentioning
confidence: 75%
“…Two qualitative studies about IUDs found that patients viewed provider selfdisclosure about IUD use positively, as it adds information about the experience of using a method, rather than medical information alone [28,30]. One quantitative study documented the potential influence of this type of communication, as it found a significant association between clinician selfdisclosure about IUD use and patients' choice of this method [32].…”
Section: Women's Preferences For Counselingmentioning
confidence: 97%